Flexible‐Dose Fesoterodine in Elderly Adults with Overactive Bladder: Results of the Randomized, Double‐Blind, Placebo‐Controlled Study of Fesoterodine in an Aging Population Trial. Issue 2 (25th January 2013) - Wagg, Adrian; Khullar, Vik; Marschall‐Kehrel, Daniela; Michel, Martin C.; Oelke, Matthias; Darekar, Amanda; Bitoun, Caty E.; Weinstein, David; Osterloh, Ian
<x xml:space="preserve">Abstract</x> Objectives To assess the efficacy and safety of flexible‐dose fesoterodine in elderly adults with overactive bladder (OAB). Design Twelve‐week, randomized, double‐blind, placebo‐controlled trial. Setting Sixty‐one outpatient clinics in Europe, Israel, and Turkey. Participants Seven hundred ninety‐four individuals aged 65 and older (47% male) with OAB symptoms for 3 months or longer, mean of eight or more micturitions and three or more urgency episodes per 24 hours, at least some moderate problems on Patient Perception of Bladder Condition (PPBC), and Mini‐Mental State Examination (MMSE) score of 20 or greater. Interventions Participants were randomized to fesoterodine or placebo for 12 weeks, with stratification according to age (>75 vs ≤75) and dosing time (morning vs evening). Participants receiving fesoterodine started on 4 mg and could increase to 8 mg at week 4 or 8 and de‐escalate to 4 mg at week 8 (sham escalation for placebo). Measurements Changes from baseline in bladder‐diary variables (primary endpoint, urgency episodes) and patient‐reported outcomes including OAB Questionnaire, Treatment Benefit Scale (TBS), PPBC, Urgency Perception Scale (UPS), and OAB Satisfaction Questionnaire (OAB‐S); all observed or reported adverse events. Results By week 8, 64% of fesoterodine‐treated and 71% of placebo‐treated participants opted for dose escalation. At week 12, the fesoterodine group had statistically significantly greater improvement than the placebo group in urgency episodes, micturitions, nocturnal micturitions, incontinence pad use, and OAB Questionnaire scores but not urgency urinary incontinence episodes. Responder rates on TBS, PPBC, UPS, and OAB‐S were statistically significantly higher with fesoterodine. Improvements in most diary variables and participant‐reported outcomes were greater with fesoterodine than placebo in participants in both age groups and when administered in the morning and evening. Rates of dry mouth and constipation were 34% and 9% with fesoterodine and 5% and 3% with placebo, respectively. Rates of adverse events and discontinuations were generally similar in participants in both age groups. There was no change in MMSE score. Conclusion Fesoterodine was associated with significantly greater improvements in most diary variables and participant‐reported outcomes than placebo and was generally well tolerated in older people.